Quality of Tour Driving License Services in Semarang Regency - Thirdy Hadmiarso; Kismartini Kismartini (Universitas Medan Area, 2020)
The Semarang Police, as a form of bureaucratic reform in services, uses a Tour Driver's Licenseservice. However, in its implementation, there are still many obstacles, namely inadequate infrastructure for Tour Driver’s License services and lack of human resources. The purpose of this study was to analyze the service quality of a Tour Driver’s License in Semarang Regency and the factors inhibiting and supporting it. This research uses a descriptive qualitative approach. The data analysis technique used is qualitative analysis (data condensation, data presentation and conclusion drawing). Based on the results of data analysis, it can be seen that the service quality of Tour Driver’s Licenses in Semarang Regency is good. Service implementers have the ability and are able to act professionally. It's just that in its implementation it is constrained by a lack of infrastructure, namely there is only one Tour Driver’s License unit, waiting chairs and tents are still not available, and a lack of human resources. There is a need for additional facilities, infrastructure and human resources to support the implementation of Tour Driver’s License services so that they are able to reach all areas in Semarang Regency.